Significance of regions in export diversification of the RF (by example of Dagestan Republic) - Z. G. Magomedova (Vestnik MGIMO-Universiteta)
Статья посвящена анализу роли регионального подхода к диверсификации экспорта для повышения международной конкурентоспособности российской экономики. Ключевые слова: диверсификация , регион,внешнеэкономические связи. The article analyses the role of regional approach to export diversification in rising international competiteveness of Russian Economy. Keywords: diversification, region, external economic relations, foreign-economic link.